Efficacy and safety of definitive chemoradiotherapy with or without induction immune checkpoint inhibitors in patients with stage III non-small cell lung cancer - Yang, Yin; Wang, Jianyang; Zhang, Tao; Zhou, Zongmei; Wang, Yu; Jiang, Ying; Liu, Wenyang; Xiao, Zefen; Deng, Lei; Feng, Qinfu; Wang, Xin; Lv, Jima; et al. (Frontiers in Immunology, 2023)
Background: In the era of immunotherapy, the optimal combination of immune checkpoint inhibitors (ICIs) and chemoradiotherapy (CRT) for stage III non-small cell lung cancer (NSCLC) is not defined. The current study investigated the efficacy and safety of definitive CRT(dCRT) plus consolidation ICIs with or without induction ICIs in stage III NSCLC. Methods: 123 consecutive patients treated with dCRT followed by consolidation ICIs at our institution from 2018 to 2022 were retrospectively reviewed. Failure patterns, survival outcomes, and toxicity profiles were analyzed. Results: The 1- and 2- year PFS rates were 75.3% and 56.9%, respectively, and median PFS was 30.83 months from the start of treatment. In-field failure (18.7%) was the most common failure pattern. The most common adverse event (AE) was pneumonitis caused by ICIs or RT. The incidence of Grade 3-4 and Grade 5 pneumonitis was 5.7% and 1.6%, respectively. Further analysis showed that the induction plus consolidation ICIs group has significantly lower cumulative incidence of distant metastasis rates (HR: 0.30, 95%CI: 0.09-1.00, p=0.043) and higher incidence of pneumonitis (p=0.039) compared with patients in the consolidation ICIs group. Conclusions: Combined CRT and consolidation ICIs achieved encouraging efficacy and manageable toxicity in patients with stage III NSCLC in China. Induction plus consolidation ICIs might reduce distant metastasis and deserve further investigation.